2010
DOI: 10.1016/s0975-3575(10)80045-8
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Screening and Antioxidant Activity of essential oil of Eucalyptus leaf

Abstract: A b s t R A c t barks, roots, fruits, buds, leaves and other parts of plant are considered as source of essential aromatic oils to cure several ailments. the antioxidant property has been shown to be important in recovery from several diseases. the essential oil extracted from eucalyptus leaves was tested for phytochemical analysis and antioxidant activities. the eucalyptus oil extracted from the leaves of Eucalyptus globulus family Myrtaceae was screened for the presence of phytochemicals and their effect on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 16 publications
3
15
0
1
Order By: Relevance
“…Tables 2 recorded the activity (using DPPH method) which increased by doubling the extract concentration (50 and 100 µg/ml). These results are in agreement with those of Mishra et al [20].…”
Section: Antioxidant Activitysupporting
confidence: 94%
See 1 more Smart Citation
“…Tables 2 recorded the activity (using DPPH method) which increased by doubling the extract concentration (50 and 100 µg/ml). These results are in agreement with those of Mishra et al [20].…”
Section: Antioxidant Activitysupporting
confidence: 94%
“…However, the glycoside and flavonoids content have the lowest value (0.2 and 0.05 % respectively). These results are in agreement with those of Mishra et al [20] who found …”
Section: Chemical Compositionsupporting
confidence: 94%
“…17 A research work has been carried out to test the antioxidant activities of Eucalyptus globulus (Myrtaceae) and the results showed that the plant is extremely beneficial. 18 The critical review of earlier works proved that the family Myrtaceae is a potential source of natural antioxidants.…”
Section: Introductionmentioning
confidence: 99%
“…The essential oils and organic plant crude extracts are of particular interest because of their safety and their wide acceptance by consumers and their uses for potential multi-purpose functional uses [2][3][4] . However [5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%